A multi-epitope vaccine targeting a key virulence factor ClfA: An In-silico approach to combat Staphylococcus aureus infections - Md. Nipatul Hasan Nirob; Ive Sultana; Tawsif Al Arian; MD. Sazidul Islam; Md Moniruzzzaman; Safia Jerin Nosi; Sajal Kumar Halder; Aparna Shil; Mahbubul Kabir Himel (PLoS ONE, 2025)
Staphylococcus aureus, a gram-positive opportunistic pathogen, presents a growing global threat due to the rise of multidrug-resistant (MDR) strains. To counter this, we designed a multi-epitope vaccine (MEV) targeting the ClfA virulence protein using an integrative in silico approach. Sixty-one conserved epitopes (19 CTL, 36 HTL, 6 LBL) were selected based on antigenicity, immunogenicity, non-toxicity, and lack of homology to human proteins. These epitopes demonstrated strong HLA-binding affinities and over 50% global population coverage, indicating broad immunological applicability. Molecular docking revealed the strongest binding between the MEV and TLR4, with a ΔG of –17.1 kcal/mol and an exceptionally low dissociation constant (2.6 × 10 ⁻ ¹² M). HADDOCK 2.4-supported docking scores corroborated these results. Molecular dynamics (MD) simulations and MM/GBSA analysis further assessed the structural behavior of the MEV in complex with TLR2, TLR3, and TLR4. While TLR2 and TLR3 complexes showed greater structural stability (RMSF ~0.2–0.5 nm), the TLR4 complex exhibited higher flexibility (RMSF ~2.5 nm) but yielded the most favorable binding free energy (ΔG = –174.41 kcal/mol), suggesting stronger overall interaction. The TLR2–vaccine complex formed ~370–400 hydrogen bonds on average, while the unbound vaccine maintained ~60–70 internal hydrogen bonds, confirming structural integrity. Radius of gyration (Rg) and solvent-accessible surface area (SASA) analyses revealed that TLR2 and TLR3 binding induced compact and stable structures, whereas the TLR4 complex was more solvent-exposed and flexible. Disulfide bond engineering (VAL32–THR37 and PHE45–ASN64) enhanced vaccine stability, further supported by favorable physicochemical parameters (MW 54.67 kDa, pI 7.78, instability index 19.78). The low eigenvalue (3.63 × 10 ⁻ ⁶) indicated high structural mobility, associated with efficient energy absorption. Codon optimization (GC content 53.33%, CAI 0.96) predicted high expression potential in E. coli , and in silico cloning was successfully performed using the pET-28a(+) vector. Immune simulation demonstrated robust humoral and cellular responses, including elevated levels of IgM, IgG1, IFN-γ, and increased B and T cell populations. Collectively, these findings suggest that the designed MEV is structurally stable, immunogenic, and capable of eliciting a potent immune response, with TLR4 emerging as a promising innate immune target. Further experimental validation and in vivo studies are essential to confirm its efficacy and safety as a vaccine candidate against S. aureus infections.